Calcium Sensing Receptors Mediate Local Inhibitory Reflexes Evoked by L-Phenylalanine in Guinea Pig Jejunum - Gwynne, Rachel M.; Ly, Kenny D. K. N.; Parry, Laura J.; Bornstein, Joel C. (Frontiers in Physiology, 2017)
Amino acids applied to the mucosa evoke inhibitory reflexes in guinea-pig jejunum, but the receptors involved in sensory transduction are still unclear. One promising candidate is the extracellular calcium sensing receptor (CaSR), which is expressed by mucosal enteroendocrine cells and is preferentially activated by aromatic L-amino acids. We tested this by applying various amino acids to the mucosa and recording the resulting inhibitory junction potentials (IJPs) in nearby circular smooth muscle via intracellular recording. The CaSR is stereospecific and L-Phenylalanine evoked a significantly larger response than D-Phenylalanine when both were applied to the same site. The same pattern was seen with L- and D-Tryptophan, another aromatic amino acid. The CaSR is preferentially activated by aromatic amino acids and responses to L-Leucine and L-Lysine were significantly lower than those to L-Phenylalanine applied to the same site. Responses to L-Phenylalanine were dose-dependently suppressed by blockade of the CaSR with NPS2143, a CaSR antagonist, and mimicked by mucosal application of cinacalcet, a CaSR agonist. Responses to cinacalcet had similar pharmacology to that of responses to L-Phenylalanine, in that each requires both P2 purinoreceptors and 5-HT receptors. L-Glutamate evoked IJPs similar to those produced by L-Phenylalanine and these were depressed by blockade of P2 receptors and 5-HT3 plus 5-HT4 receptors, but NPS2143 was ineffective. The AMPA receptor antagonists DNQX (10 μM) and CNQX (10 μM) reduced IJPs evoked by L-Glutamate by 88 and 79% respectively, but neither BAY367260 (mGluR5 antagonist) nor 2APV (NMDA antagonist) affected IJPs evoked by L-Glutamate. We conclude that local inhibitory reflexes evoked by aromatic L-amino acids in guinea pig jejunum involve activation of CaSRs which triggers release of ATP and 5-HT from the mucosa. L-Glutamate also evokes inhibitory reflexes, via a pathway that does not involve CaSRs. It is likely there are multiple receptors acting as sensory transducers for different luminal amino acids.